Acehnese adolescents’ awareness of Acehnese idiom and simile - Ida Muliawati; Nyak Mutia Ismail; Fera Busfina Zalha (Studies in English Language and Education, 2019)
Acehnese language is rich in its figurative languages such as in forms of idioms and similes. Acehnese people have been magnifying the idioms and similes over decades to soften utterances, and they are inherited from generation to generation. Consequently, this study aimed at investigating Acehnese adolescents’ understanding of Acehnese idioms and similes. Qualitative research designed was used, and data were collected through a questionnaire consisting of 10 Acehnese figurative language expressions. There were 51 respondents, aged within 18-21 years old who all are indigenous Acehnese. The result suggests that Acehnese adolescents are still knowledgeable about them. There is 72.8% of respondents who are considered to understand the idioms asked in the questionnaire set. Meanwhile, those who did not understand the expressions come from different language continuum areas. In conclusion, Acehnese adolescents are still aware of the Acehnese figurative language, and this positivity shall help in preserving the values of Acehnese language for the next generation to come.